The Republic of Macedonia in the End of the XX and the Beginning of the XXI Century - International Recognition and the Difficult Path to NATO and the EU - Stamova, Mariyana (Research Papers, 2019)
While the last decade of the XX century is primarily related to international recognition of the Republic of Macedonia, the first decade of the XXI century the country faces both serious cross-national problems and contradictions mainly between Macedonian and Albanian ethnic group in the country, as well as the dilemma about its prospects for membership in the Euro-Atlantic structures - the EU and NATO. The Ohrid Agreement brought to life a new constitutional concept of a multiethnic society and the Albanians have become a key institutional factor.
Keywords: Republic of Macedonia; Ohrid agreement; Cross-national relations; EU; NATO